The evaluation of the quality of life in survivors of critical illness after discharge from Intensive Care Unit (ICU): A prospective cohort study - Papageorgiou, Dimitrios; Triantafyllou, Christos; Stavropoulou, Areti; Kelesi, Martha; Kaba, Evridiki; Evgenikos, Konstantinos; Liveri, Athanasia; Stroumpouki, Theodora (Health & Research Journal, 2024)
Background: Admission to the Intensive Care Unit (ICU) constitutes a substantial psychophysical burden for patients and their relatives. Individuals who are critically ill and receive care in the ICU frequently exhibit numerous physical and mental issues stemming from the primary ailment, its complications, and subsequent treatments. Aim: This study aimed to assess the quality of life (QoL) for ICU patients in the first and third month after ICU discharge and identify any issues arising from their ICU hospitalization. Method and Material: This was a prospective cohort study. The study participants were adult medical or surgical patients admitted to ICUs in three public hospitals in the region of Attica in Greece, from August 2020 to December 2021. The short form (SF)-36 was used to measure QoL. Data collection was performed through telephone interviews during the first and third month after ICU discharge. Results: The study included 43 patients. The mean age was 59.63±13.06 years. The average value of the two main categories in the 1st month was: Physical health: 53.72 ± 15.92, and Mental health: 69.03 ± 26.02, while in the 3rd month, it was 62.42 ± 20.45 and 72.81 ± 16.47, respectively. The duration of mechanical ventilation, high-flow oxygen therapy, and spontaneous breathing in days seemed to be correlated with the “Physical Functioning”, “Pain”, and “Limitation of the role due to Physical health” subscales of SF-36, respectively (p-value <0.05). The total length of hospitalization seemed to have a statistically significant weak negative correlation with "Physical Function" and "Physical Health" subscales (p-value<0.05). Conclusions: An improvement in patients’ QoL was demonstrated three months after discharge from the ICU.